Well-defined hierarchical teddy bear sunflower-like NiCo2O4 electrocatalyst for superior water oxidation - Bodhankar, Pradnya M. M.; Dhawale, Dattatray S. S.; Giddey, Sarbjit; Kumar, Ravi; Sarawade, Pradip B. B. (Sustainable Energy & Fuels, 2022)
The development of a robust and efficient electrocatalyst for water oxidation is challenging due to the large overpotential requirement to transfer four electrons. Herein, a novel spinel-type hierarchical teddy bear sunflower-like NiCo2O4 electrocatalyst was synthesized through the facile solvothermal process and evaluated for the challenging and demanding oxygen evolution reaction (OER) in the water electrolysis process. The teddy bear sunflower-like NiCo2O4 supported on nickel foam (NF) delivers a current density of 50 mA cm(-2) at a small water oxidation overpotential (eta(50) = 319 mV) which is significantly lower than that of the corresponding spherical NiO/NF (eta(50) = 338 mV), and sea-urchin like Co3O4/NF (eta(50) = 357 mV). A large specific and electroactive surface area, as well as a high TOF value exhibited by the hierarchical teddy bear sunflower-like NiCo2O4 electrocatalyst, demonstrates the potential of NiCo2O4 to catalyze the water oxidation reaction efficiently. The impact of the near-Fermi-level d-orbital states in NiCo2O4 electrocatalyst for boosting OER activity was unveiled by the density functional theory calculation. The stable performance even after 16 h and high catalyst utilization of the hierarchical teddy bear sunflower-like NiCo2O4 through the OER indicates that the catalyst is highly suitable for the large-scale water oxidation process.